Peningkatan Karakter Gotong Royong Melalui Model Problem Based Learning pada Pembelajaran Pendidikan Pancasila di Kelas V SD Negeri 060937 Medan Joror - Sari, Permata; Amin, Teguh Satria; Kartolo, Rahmad; Fahlevi, Putra (Indo-MathEdu Intellectuals Journal, 2025)
The lack of strong cooperative character among students at SD Negeri 060937 Medan Johor is due to their insufficient development of teamwork skills during collaborative tasks in the learning environment. Thus, it is essential for teachers to implement creative teaching methods. This research aims to enhance the cooperative character of students using the Problem Based Learning approach within the Pancasila Education subject for fifth graders at SD Negeri 060937 Medan Johor. The study is structured as Classroom Action Research (PTK) including a preliminary phase, followed by two cycles. Data collection methods comprised observations, interviews, surveys, and documentation, which were analyzed both quantitatively and qualitatively. The participants were 26 fifth-grade students from SD Negeri 060937 Medan Johor. The outcomes of this research reveal a positive development in the students' cooperative character through the Problem Based Learning methodology, with learning achievements rising from 53% in the first cycle to 84% in the second cycle, indicating an improvement of 31%. These results support the conclusion that the Problem Based Learning framework can foster increased mutual cooperation among students.